Enhancing Technical Competency in Naval Engine Systems through Industry-Based Learning in Maritime Vocational Education - R.Herlan Guntoro; Pargaulan Dwikora Simanjuntak (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This research explores the enhancement of technical competency in naval engine systems through industry-based learning approaches within maritime vocational education. Employing a qualitative descriptive method, the study involved two participant groups: experienced maritime professionals with over 20 years of sea service who now serve in managerial, advisory, and auditing roles in port and shipping industries, and ten vocational lecturers with sea-going experience and extensive teaching expertise in marine engineering. Findings revealed a substantial gap between classroom-based theoretical instruction and the practical realities of engine room operations. Contributing factors include outdated curricula, limited industry engagement in teaching processes, and insufficient access to real-life engine room practice. Both professionals and educators highlighted the urgency of integrating experiential learning models to align educational outcomes with industry demands. The study emphasizes the need for curriculum reform grounded in real-world operations, competency-based assessment methods, and structured mentorship from industry practitioners. By bridging the disconnect between institutional instruction and shipboard operations, this research contributes a strategic framework for developing adaptive, skilled, and industry-ready maritime graduates in engine systems.